Medicine and duty : the World War I memoir of Captain Harold W. McGill, Medical Officer, 31st Battalion, C.E.F. - McGill, Harold, 1879-1961 (Legacies shared book series, 2007)
"Medicine and Duty" is the World War I memoir of Harold McGill, a medical officer in the 31st Alberta Battalion, Canadian Expeditionary Force, that was originally compiled and written by McGill in the 1930s. Anticipating that his memoir would be published by Macmillan of Canada in 1935, McGill instead was met with disappointment when the publishing house, forced by financial constraints, was unable to see the project to its final conclusion.; Decades later, Editor Marjorie Norris came upon a draft of the manuscript in the Glenbow Museum Archives, and utterly compelled by what she found, took it upon herself to resurrect McGill's story. Performing an exhaustive edit of the original manuscript, Norris has also included a wealth of information adding detailed explanatory notes and topographical maps, as well as excerpts of letters Captain McGill sent home to friends and family. These letters are literally written "from the trenches" and lend an unsettling atmosphere and stark realism to the original memoir.; Wartime accounts written by medical officers are quite rare, and often more than other regular officers, the MO's position in the battalion provides a unique perspective on the day-to-day lives of soldiers under his command. Norris' painstaking archival research and careful editing skills have brought back to light a gripping first-hand account of the 31st Battalion and, on a larger scale, of Canada's participation in World War I, making this book of great interest not only to military historians, but also to any Canadian compelled by the incredible sacrifice of soldiers during wartime